Dinamika identitas etnis dan identitas nasional dalam proses menjadi orang Indonesia: Studi pada etnis Batak - Meutia Nauly; Irmawati Irmawati; Ridhoi Meilona Purba; Rahma Fauzia (Jurnal Psikologi Ulayat, 2022)
This qualitative study is particularly focused on the North Sumatera context; it investigates the dynamics of ethnic and national identities of Bataknese youths in the defining themselves as an Indonesian. Thirty-one individuals (six local figures and 25 Bataknese youths) participated in the study. The results illustrated the strengthening process of ethnic identity through exploring family and environmental common practices. The strengthening of ethnic identity was also found to occur in concurrent with the strengthening of national identity, as manifested in the participants’ willingness to maintain harmony in their society. The study concludes that the strengthening of ethnic identity positively shapes one’s national identity. Student participants and local figures expressed concern about the sustainability of cultural cultivation which is necessary to shape ethnic identity among young Bataknese. The study recommends a Batak kinship model known as dalihan na tolu, in which many families with different tasks and roles, flexibly manage differences to strengthen national identity based on the philosophy of Bhinneka Tunggal Ika.